Students with intellectual and developmental disabilities in inclusive higher education: perceptions of stakeholders in a first-year experience. Issue 9 (29th July 2021) - Brewer, Robin; Movahedazarhouligh, Sara
ABSTRACT: Post-secondary education and students with intellectual and developmental disabilities (ID/DD) have not historically been viewed as compatible. In recent years, a growing number of colleges have offered opportunities for students with intellectual disabilities to take part in inclusive post-secondary education. This qualitative study was conducted on the performance of a first-year, post-secondary inclusive education programme in a university in the United States to (a) better understand each stakeholder group's perspectives regarding both social and academic inclusion of students with ID/DD in post-secondary education, (b) identify barriers, challenges, strengths and needs of the programme through the first-year experiences and, (c) report on the successful inclusion of students in an inclusive post-secondary environment. Recommendations and learned strategies are also discussed.